Retention of Dry Matter, Organic Matter and Nitrogen In Native Chicken Fed Non-AGP Rations Added by Rubber Leaf (Hevea Brasiliensis) Flour - Muhammad Arif Marla; Sri Wigati; Fahmida Manin; Yatno (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2021)
The purpose of the study was to determine the effects of adding rubber leaf flour (Hevea brasiliensis) to non-antibiotic growth promoter (non-AGP) commercial rations on dry matter, organic matter and nitrogen retention in native chickens. The materials used were 64 native chicken (32 male and 32 female) aged 8 weeks, non-AGP commercial ration and rubber leaf flour. The experimental design used was a Randomized Block Design (RBD) with 4 treatments and 8 replications. Grouping based on sex, and each replication unit consisted of 2 chickens. The treatment given was the addition of rubber leaf flour by 0% (P0), 3% (P1), 6% (P2) and 9% (P3) in a 100% commercial ration. The observed variables were dry matter (DM), organic matter (OM) and nitrogen (N) retention. Data were analyzed using analysis of variance, and the results showed that the addition of rubber leaf flour in the rations had no significant effect (P>0.05) on the observed variables. Retention of Dry Matter, Organic Matter and Nitrogen in treatment groups of P0, P1, P2 and P3 were respectively: 75.40, 78.45, 77.54 and 77.64%; 77.92, 78.38, 78.84 and 77.48 %; and 53.67, 57.69, 54.53 and 56.45%. In conclusion, the use of rubber leaf flour up to the level of 9% can highly enhance the retention of DM, OM and Nin native chicken, and hence it will also open and facilitate its potency as herbal feed additive as alternative to synthetic- AGP. Keywords: Hevea brasiliensis, Native chicken, Non-AGP rations, Rubber leaves